Adaptation, integration and acculturation of foreign athletes in sports organizations in Romania and France - Daniel Lovin; Alexandru Căpățînă; Denis Bernardeau Moreau (Nicolaus Copernicus University in Toruń, 2021)
We live in an increasingly globalized and culturally diverse society, in which individuals with different cultural backgrounds, different education, different personalities and different values must work together and achieve optimal results. Moreover, these cultural differences are noticeable even within a group of people of the same nationality. At the same time, lately there are more and more bicultural individuals, who belong simultaneously to different cultures. Nowadays, sport has an enormous impact on society, being an extremely popular phenomenon on a global scale and which has become a business in which huge sums are spent. Sport can have both a unifying effect, bringing together different individuals, but at the same time it can emphasize cultural differences and deep ethnic differences. All these arguments justify the increased interest in multiculturalism in general, and in multiculturalism in sport in particular. Using SPSS software, this study proposes a quantitative comparative analysis of how the country in which athletes evolve, namely Romania and France, influences adaptation, self-confidence, team integration and market share of athletes.